2021
DOI: 10.1080/10717544.2021.1938758
|View full text |Cite
|
Sign up to set email alerts
|

Development of thermosensitive poloxamer 407-based microbubble gel with ultrasound mediation for inner ear drug delivery

Abstract: Our previous study first investigated feasibility of applying ultrasound (US) and microbubbles (MBs) via external auditory canal to facilitate drug delivery into inner ear. However, most drugs are in aqueous formulae and eliminated via Eustachian tubes after drug application. In this study, feasibility of sustained release of thermosensitive poloxamer 407 (P407)-based MB gel for US mediation-enhanced inner ear drug (dexamethasone, DEX) delivery was investigated. The sol-to-gel transition temperature showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Poloxamer 407, also referred to as Pluronic F-127, has good biocompatibility and is widely used as a drug delivery vehicle (Moura et al, 2020;Liao et al, 2021). It is reported that PEO-PPO-PEO hydrogel Pluronic F127 can load recombinant adenoassociated virus (rAAV) vectors overexpressing the chondrogenic sox9 transcription factor (rAAV-FLAG-hsox9), which form an injectable and thermosensitive therapeutic Frontiers in Pharmacology frontiersin.org hydrogel capable of sustained release of rAAV-FLAG-hsox9 (Madry et al, 2020).…”
Section: Poloxamer Micellar Systemmentioning
confidence: 99%
“…Poloxamer 407, also referred to as Pluronic F-127, has good biocompatibility and is widely used as a drug delivery vehicle (Moura et al, 2020;Liao et al, 2021). It is reported that PEO-PPO-PEO hydrogel Pluronic F127 can load recombinant adenoassociated virus (rAAV) vectors overexpressing the chondrogenic sox9 transcription factor (rAAV-FLAG-hsox9), which form an injectable and thermosensitive therapeutic Frontiers in Pharmacology frontiersin.org hydrogel capable of sustained release of rAAV-FLAG-hsox9 (Madry et al, 2020).…”
Section: Poloxamer Micellar Systemmentioning
confidence: 99%
“…Recently, the permeabilization of RWM to fluorescent markers (Biotin-FITC, Texas-red-labelled gentamicin) or therapeutic molecules (plasmid DNA, dexamethasone, and insulin growth factor 1) using sonoporation has been successfully reported in vitro and in guinea pig models [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. These studies described acoustic protection when applying dexamethasone [ 28 , 31 ] and a better uptake by vestibular hair cells when applying gentamicin [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the permeabilization of RWM to fluorescent markers (Biotin-FITC, Texas-red-labelled gentamicin) or therapeutic molecules (plasmid DNA, dexamethasone, and insulin growth factor 1) using sonoporation has been successfully reported in vitro and in guinea pig models [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. These studies described acoustic protection when applying dexamethasone [ 28 , 31 ] and a better uptake by vestibular hair cells when applying gentamicin [ 29 ]. The efficiency of acoustically mediated drug delivery depends on the application route of ultrasound (e.g., transcanal or transcranial) and ultrasound parameters, including the central frequency, the duty cycle, the acoustic intensities, and the exposure time [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…One limitation to this approach is that dexamethasone is rapidly cleared from the middle ear [ 7 ]. Thus, strategies to provide sustained delivery of dexamethasone to the inner ear are an active area of research [ 8 , 9 ]. While retention of synthetic glucocorticoids in the ear may provide greater therapeutic benefits, the effects of prolonged dexamethasone exposure on hair cell organ homeostasis and function are not well defined.…”
Section: Introductionmentioning
confidence: 99%